A Cross-Sectional Study of Prevalence of Gastro-Oesophageal Reflux Disease and Associated Risk Factors Among Medical Students of Pakistan - Sana Fatima, Roumman Ashraf (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Gastroesophageal reflux disease (GERD) is a common condition involving the backward flow of stomach contents into the esophagus, causing symptoms like heartburn and regurgitation. If untreated, it can lead to complications such as Barrett’s esophagus and esophageal cancer. Risk factors include stress, obesity, poor diet, smoking, and NSAID use. GERD affects 13.98% of the global population, with up to 24% prevalence in Pakistan. Medical students are especially vulnerable due to academic stress, sedentary routines, and irregular meals. However, limited data exists on GERD in this group. This study aims to evaluate its prevalence, risk factors, and impact on medical students’ daily life. Objectives: To evaluate the prevalence of GERD among medical students in Pakistan. To assess the risk factors and the impacts of GERD on the lives of medical student. To suggest necessary lifestyle modifications to reduce symptoms of GERD. Method: A nationwide study was conducted among undergraduate medical students. Using Cochran formula, the calculated sample size was 220 students (CI-95%; ERR-5%).Non-random convenience-based sampling was applied, electronic pretested questionnaire was distributed to various medical institutes in May 2024. It comprised questions regarding demographic data, risk factors, GERD Questionnaire, and 10-item-Cohen’s perceived stress scale (PSS). IBM SPSS, version-27 employed for data analysis. Participants with cut-off value ≥ 8 were considered having GERD. Scores 0-13, 14-26, 27-40 were classified low, moderate, and high perceived stress. Association between categorical values was evaluated using Pearson’s Chi Square test. Approval was obtained from Ethical Review Committee of Rawalpindi Medical University; informed consent was taken, anonymity was maintained. Result: Total 249 responses were received, majority being females 212 (85.1%) and 189 (75.9%) having healthy BMI (18-25 kg/m2). Prevalence of GERD calculated was 20.5% (n=51). Similarly, 178 (71.5%) and 31 (12.4%) participants reported experiencing moderate and high perceived stress respectively. Statistically Prevalence of GERD was significantly associated with midnight snacking (p-value= 0.007), mode of exercise (p-value=0.034), and perceived stress (p-value= 0.025). Conclusion: Gastroesophageal reflux disease is prevalent among medical students, attributed to stress and unhealthy lifestyle habits. Despite limitations such as recall bias and lack of formal diagnosis, this study contributes valuable insights to existing research. Raising awareness of the risk factors and management strategies is essential to mitigate the increasing prevalence of the disease, particularly among future healthcare professionals. Keywords: Gastroesophageal Reflux (D005764), Gastric Acid (D005744), Esophagitis (D004941), epidemiology (Q000453)